Prevalence of Trachoma and Access to Water and Sanitation in Benue State, Nigeria: Results of 23 Population-Based Prevalence Surveys. (28th December 2018) - Mpyet, Caleb; Tagoh, Selassie; Boisson, Sophie; Willis, Rebecca; Muhammad, Nasiru; Bakhtiari, Ana; Adamu, Mohammed D.; Pavluck, Alexandre L.; Umar, Murtala M.; Alada, Joel; Isiyaku, Sunday; Adamani, William; et al.
ABSTRACT: Purpose : We sought to determine the prevalence of trachoma in each local government area (LGA) of Benue State, Nigeria. Methods : Two-stage cluster sampling was used to conduct a series of 23 population-based prevalence surveys. LGAs were the evaluation units surveyed. In each LGA, 25 households were selected in each of 25 clusters, and individuals aged 1 year and above resident in those households were invited to be examined for trachoma. Data on access to water and sanitation were also collected at household level. Results : A total of 91, 888 people were examined from among 93, 636 registered residents across the 23 LGAs. The LGA-level prevalence of trachomatous inflammation—follicular (TF) in 1–9 year olds ranged from 0.3% to 5.3%. Two LGAs had TF prevalences of 5.0–9.9%. The LGA-level prevalence of trichiasis in ≥15-year-olds ranged from 0.0% to 0.35%. Access to improved drinking water sources ranged from 0% in Gwer West to 99% in Tarka, while access to improved sanitation ranged from 1% in Gwer West to 92% in Oturkpo. Conclusion : There is a need for public health-level interventions against trachoma in three LGAs of Benue State.